A Framework for the Static and Interactive Visualization of Statecharts - Castelló, Rodolfo; Mili, Rym; Tollis, Ioannis (Journal of Graph Algorithms and Applications, 2002)
We present a framework for the automaticgeneration of layouts of statechart diagrams. Statecharts []are widely used for the requirements specification of reactive systems.Our framework is based on several techniques that include hierarchicaldrawing, labeling, and floorplanning, designed to work in a cooperativeenvironment. Therefore, the resulting drawings enjoy severalimportant properties: they emphasize the natural hierarchicaldecomposition of states into substates; they have a low number ofedge crossings; they have good aspect ratio; and require a smallarea. We also present techniques for interactive operations.We have implemented our framework and obtained drawings forseveral statechart examples. <!---->